Intraseasonal Changes in Switchgrass Nitrogen Distribution Compared with Corn. (1st March 2013) - Wilson, Danielle M.; Heaton, Emily A.; Liebman, Matt; Moore, Kenneth J.
Abstract : Incorporating perennial, bioenergy crops like switchgrass ( Panicum virgatum L.) into agricultural landscapes can provide harvestable biomass while improving ecosystem functions, but clear plant N management recommendations for switchgrass remain elusive. Delaying harvest until spring can reduce plant N concentration ([N]) but also harvestable yield, creating a tradeoff between feedstock quality and quantity. This study investigated internal changes in the temporal and spatial distribution of N in switchgrass tissues. Above‐ and belowground switchgrass biomass was harvested at five dates annually from field plots in central Iowa for 2 yr. The [N] of aboveground tissues decreased during the growing season, with no further change over winter. The [N] of belowground biomass tissues found within the upper strata (0–45 cm) of the soil profile increased significantly from July to October ( P = 0.0050), suggesting seasonal N translocation. Plots harvested at peak biomass, before senescence, yielded significantly less the following season ( P < 0.0001), suggesting that this harvest strategy would not be sustainable in the long term. Although delaying harvest to after frost reduced the harvested biomass, less N was removed with the harvest, more was stored in belowground tissues, and yields were more similar between years. A postfrost switchgrass harvest would remove much less N during a 2‐yr period compared with continuous corn ( Zea mays L.) with 50% stover removal (57.7 vs. 432.2 kg N ha −1 ). Results provide values of N stocks and fluxes in switchgrass tissues, showing the tradeoffs between feedstock quality and quantity.